PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN HARGA TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN MIE GACOAN DI KOTA KENDARI - Muhayyang; Rahmat Madjid; Hayat Yusuf; Dzulfikri Azis Muthalib (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the effects of product quality, service quality, and price on customer loyalty, with customer satisfaction as a mediating variable, among Mie Gacoan customers. A quantitative method was used, and the author employed purposive sampling to obtain the sample for this study. The sample consisted of 110 respondents. Data were collected via a Likert-scale questionnaire and analyzed using SmartPLS 4. The results indicate that product quality and service quality have a positive and significant effect on customer satisfaction and customer loyalty toward Mie Gacoan. Meanwhile, price has a negative and significant effect on customer loyalty toward Mie Gacoan. Price, on the other hand, has a negative but insignificant effect on customer satisfaction with Mie Gacoan in Kendari City. Furthermore, the results of the mediation test indicate that customer satisfaction mediates the effects of product quality and service quality on customer loyalty toward Mie Gacoan in Kendari City. However, customer satisfaction does not mediate the effect of price on customer loyalty toward Mie Gacoan in Kendari City.